PENGGUNAAN MODEL INFORMATION SEARCH UNTUK MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS PENGGUNAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SEKOLAH SDIT ULIL ALBAB PEMATANGSIANTAR - Simanjuntak, Melvin; Desi Gultom; Lila Liza Irfany Siregar; Ruth Oppusunggu; Adelina Purba; Dwi Dinda; Maria Simbolon; Hildawati Tinambunan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to describe the application of transparency in the use of school operational assistance funds (BOS) in SDIT Ulil Albab Pematangsiantar and to describe the application of accountability for the use of school operational assistance funds (BOS) in SDIT Ulil Albab Pematangsiantar. quantitative using questionnaires, instruments and observations, interviews and documentation. Data analysis techniques used data reduction, data exposure and drawing conclusions. Checking the validity of the data using the triangulation technique. The results showed that the application of the principle of transparency in the use of BOS funds in SDIT Ulil Albab Pematangsiantar. When the use of BOS funds was carried out openly, it could be seen that the process of using it was reported to the Education Office offline and online. Reporting on the use of BOS funds is carried out by preparing quarterly financial reports. The publication of reports is carried out through meetings and can also be accessed online via the official E-Bos website. The application of the principle of accountability for the use of BOS funds by SDIT Ulil Albab Pematangsiantar, on the use of BOS funds is in accordance with Permendikbud No.3 of 2019 concerning the technical guidelines for BOS funds which are government policies, in terms of being responsible for schools to prepare financial reports as a form of accountability. With this accountability, it is a reflection that schools have implemented the principle of accountability so that it fosters trust by the community in schools.